Structural Equation Modeling of Adherence to Treatment Based on Cognitive Function Mediating Role of Coping Strategies in Women with Breast Cancer Undergoing Chemotherapy - Abdoli, Faranak; Ebrahim Madahi, Mohammad; Seyrafi, Mohammadreza (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:The present study aimed to investigate the structural equations of treatment adherence based on cognitive function mediated by coping styles in women with breast cancer undergoing chemotherapy. Materials and Methods:The present study was correlational and structural equation modeling. The statistical population included patients with breast cancer referred to specialized cancer clinics in Tehran between October and February 2017. The sample consisted of 250 patients with breast cancer who were selected by voluntary sampling. Data were obtained using the Folkman and Lazarus Coping Strategies Questionnaire, the Cognitive Function Questionnaire, and Morisky Medication Adherence Scale (MMAS-8). Data were also analyzed using correlation coefficient, Pearson correlation matrix, multiple regression, and structural equation modeling. Also, all statistical calculations were performed using Amos.22 and SPSS.22 software. Results:The results showed that cognitive function had a direct effect on coping strategies (β=0.48, P<0.001) and adherence to treatment (β=0.63, P<0.001). Coping strategies had a mediating role in the relationship between cognitive function and adherence to treatment. Conclusion:It can be concluded that cancer and the patient’s necessity to follow treatment cause many challenges in daily life that necessitate the use of coping styles to adapt, coping styles play an important role in the course, control and psychosocial adjustment of the patient with cancer can have